Superman Doomsday. - Bruce, Timm.; Duane, Capizzi; Lauren, Montgomery; Brandon, Vietti; Warner Bros. Animation; Warner Home Video (Firm).; Warner Home Video (Phils.). (Burbank, Calif. Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.), 2007)
When Lexcorp accidentally unearths the intergalactic serial killer Doomsday, Superman must battle the creature head-on in the fight of his life. The world collectively mourns their fallen hero and humanity realizes it will never feel truly safe again. Superman's enemies rejoice, all but Lex Luthor, who grieves the loss in his own demented manner, setting off a chilling chain of events that even he couldn't have foreseen.
Based on the graphic novel.
Editor, Joe Gall ; music, Robert J. Kral ; art direction, Bruce Timm.
Voices: Adam Baldwin, Anne Heche, James Marsters, John Di Maggio, Tom Kenny, Swoosie Kurtz, Cree Summer, Ray Wise, Adam Wylie.
MPAA rating: PG-13.
VCD
Keywords: Superman -- (Fictitious character) -- Drama; Jurgens, Dan -- Film and video adaptations; Serial murderers -- Drama; Good and evil -- Drama; Death -- Psychological aspects -- Drama